Bibliometric Analysis of Research of Genderlect Communication in 2019-2024 on Google Scholar - Rahardipta, Danar Drestanto (KOMUNIKA, 2024)
This study aims to analyze the development of research on the topic and title of genderlect by linking emerging concepts through keywords, to provide references for researchers to understand trends in research on genderlect. The method used is a bibliometric analysis of research titled genderlect published between 2019 and 2024, sourced from the Google Scholar database. VOSviewer was applied to conduct the bibliometric analysis of these articles. The results show that 29 studies with the title "genderlect" from 2019 to 2024 were indexed online in Google Scholar, of which 9 did not have a publication year and were therefore not included in the bibliometric data analysis. The co-authorship analysis results indicate that there were only connections among researchers with the same research title, and no correlated relationships among researchers with different research titles on genderlect studies from 2019 to 2023. Meanwhile, the co-occurrence analysis results show that the keyword genderlect was frequently used in research during the 2019 to 2023 period, while keywords such as feminist linguistics or education were rarely used, indicating that there are still opportunities for research on these topics related to genderlect.